Women in Military in India: The Cry for Parity - Bhattacharyya, Arundhati (Mediterranean Journal of Social Sciences, 2012)
Gunnar Myrdal in his â€œAsian Dramaâ€ argued that the traditional societies cannot modernize themselves, unless theyrecast their traditional institutions, beliefs and values, to suit the demands of development. But, India has proved that it is notnecessarily true, particularly, in the restructuring of gender relations in the workplace. Women have proved their worth, not to theexclusion of their male counterparts. But, Indian women have distinguished themselves by working shoulder to shoulder withmen. Yet, the women made their own mark and proved a cut above the rest in so many areas of performance. The Indian Statehas also supported them. In the final document of the Vienna Conference, States formally recognized the human rights ofwomen to be an integral, inalienable and indivisible part of universal human rights. They further demanded that the equal statusof women and the human rights of womenâ€¦be integrated into the mainstream ofâ€¦.the United Nations human rights activities.